Sistem Pendukung Keputusan Pemilihan Komputer Mining Rig Dengan Metode COPRAS - Rahartyan Wisnu Herlambang; Jati Sasongko Wibowo (STEKOM PRESS, 2022)
Computer mining rigs are specially designed for only one purpose which is to mine crypto assets efficiently and effectively. Mining takes a lot of time, therefore it is very important to pay attention to computers for mining. The better the quality of the PC or computer, the faster the mining process will be. So far, consumers in choosing a mining rig computer only observe the mining rig computer without looking at special criteria such as price, motherboard, processor, VGA, power supply and RAM. COPRAS method assessment criteria include price criteria, motherboard, processor, VGA, power supply and RAM.. The system development method uses a prototype, the system design uses UML and the system manufacture uses PHP and MySQL. The results of the computer mining rig recommendations calculated using the COPRAS method are 12 GPUs 381 mh/s with a value of Ui = 1,000, Rig RTX 2060 with a value of Ui = 0,8157, Rig 6 x RTX 3060 with a value of Ui = 0,7108 and Rig RTX 2060 II with a value of Ui = 0.7014..